Deoxyribozyme‐Based DNA Machines for Cancer Therapy. (17th October 2019) - Nedorezova, Daria D.; Fakhardo, Anna F.; Molden, Tatiana A.; Kolpashchikov, Dmitry M.
Abstract: Soon after their discovery, RNA‐cleaving deoxyribozymes (RCDZ) were explored as anticancer gene therapy agents. Despite low toxicity found in clinical trials, there is no clinically significant anticancer RCDZ‐based therapy. Some of the reported disadvantages of RCDZ agents include poor accessibility to folded nucleic acids, low catalytic efficiency inside cells, and problems of intracellular delivery. On the other hand, structural DNA nanotechnology provides an opportunity to build multifunctional nano‐associations that can address some of these problems. Herein we discuss the possibility of building RCDZ‐based multifunctional DNA nanomachines equipped with RNA unwinding, cancer marker recognition, and RCDZ‐based RNA‐cleavage functions. An important advantage of such "nanomachines" is the possibility to cleave a housekeeping gene mRNA in a cancer‐cell‐specific manner. The proposed design could become a starting point for building sophisticated DNA‐based nanodevices for cancer treatment. Abstract : Fire the housekeeper : The deoxyribozyme‐based DNA machine is an association of several DNA strands that can recognize a fragment of a cancer cell marker and use it for activation of the RNA‐cleaving function. Cleavage of housekeeping gene mRNA can cause cancer cell death. Such nanomachines could therefore be used to treat cancer.